Implementasi PHBS Anak Kelompok A Dalam Pembelajaran Storytelling: Studi Kasus Kemampuan Bahasa Reseptif Dan Ekspresif - Hanifatun Nisak; Soraya Rosna Samta; Sri Setiyo Rahayu (Universitas Ivet, 2026)
Early childhood health literacy is essential for shaping clean and healthy living habits, yet children often struggle to understand health messages due to limited receptive and expressive language skills. This study aimed to describe the implementation of the storytelling method in improving the receptive and expressive language abilities of group A children in relation to health literacy. The research used a descriptive qualitative case study approach involving 14 children at RA Manda. Data were collected through participatory observation, in-depth interviews with teachers, and documentation of children’s developmental portfolios. The findings show that contextual storytelling stimulated children’s ability to listen to storylines, understand PHBS instructions, answer guiding questions, retell the story, and express emotions and messages from the characters. The auditory and visual stimulation structured by the teacher helped children transform abstract health concepts into concrete understanding. The study concludes that health-literacy-based storytelling is an effective linguistic bridge for optimizing early childhood receptive and expressive language development.